2011
DOI: 10.1021/la2002496
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-Based Aluminum Ion Sensing Using a Surface-Functionalized Microstructured Optical Fiber

Abstract: The first microstructured optical fiber-based sensor platform for aluminum ions using a surface-attached derivative of lumogallion (3), a known fluorescence-based indicator, has been fabricated. These fibers allow for strong evanescent field interactions with the surrounding media because of the small core size while also providing the potential for real-time and distributed measurements. The fluorescence response to aluminum ions was first demonstrated by applying the procedure to glass slides. This was achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 23 publications
0
53
1
Order By: Relevance
“…This fluorescence was similar to that previously reported for Azo1 in water and on poly(allylamine hydrochloride) coated fibre surfaces. [25] The photodecay study showed that in DMSO solution the fluorescence intensity of Azo1 decreased by 33% over the first ten pulses relative to the initial intensity ( Figure 3B). This rapid decrease in fluorescence is likely due to photobleaching rather than from trans to cis photoisomerisation, as the original fluorescence spectrum was unable to be regenerated thermo-or photochemically after prolonged exposure with white or UV light; as would be expected if photochromism was occurring.…”
Section: Azobenzenementioning
confidence: 92%
See 2 more Smart Citations
“…This fluorescence was similar to that previously reported for Azo1 in water and on poly(allylamine hydrochloride) coated fibre surfaces. [25] The photodecay study showed that in DMSO solution the fluorescence intensity of Azo1 decreased by 33% over the first ten pulses relative to the initial intensity ( Figure 3B). This rapid decrease in fluorescence is likely due to photobleaching rather than from trans to cis photoisomerisation, as the original fluorescence spectrum was unable to be regenerated thermo-or photochemically after prolonged exposure with white or UV light; as would be expected if photochromism was occurring.…”
Section: Azobenzenementioning
confidence: 92%
“…Members of these classes are known to have high fatigue resistance, an ability to operate at biologically compatible wavelengths, and well-defined switching states that exhibit large conformational differences; making them suitable for applications in devices. Azobenzenes and spiropyrans have already found use in MOF devices, [23][24][25][26][27] while the indolylfulgide (CF 3 -fulgide) and diarylalkene (DA1) show promising properties in terms of high photoswitching fatigue resistance, a large spectroscopic change upon photoswitching, and tunable absorption profiles within the visiblered region. [28][29][30] In this context, we recently reported the use of 3-carboxy-5,2',4'-trimethoxy azobenzene (Azo1) in combination with a MOF for the sensing of aluminium ions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A protected core geometry is necessary for sensing in harsh environments such as the application under consideration in this paper. In particular, the suspended-core fibre [12] design, which consists of a small glass core suspended by thin struts inside voids within the fibre, have found extensive use in chemical sensing applications [8,13]. For these fibres the PF overlaps with the voids, and by controlling the size of the core, this overlap between the light and the voids can be adjusted.…”
Section: Microstructured Optical Fibres (Mofs)mentioning
confidence: 99%
“…The resulting fluorescence is collected by the optical fiber and is taken to a photodetector or spectrum analyzer for recording and analysis. Fiber-based fluorescence sensing has been deployed in sensing targets such as: aluminum ions [7], hydrogen peroxide [8], oxygen [9], and explosives [10]. Optical fiber based fluorescence sensors have also been deployed for biological applications, including measurements of biomolecules in solution [11], DNA [12], or enzyme assays within microstructured fibers [13].…”
Section: Introductionmentioning
confidence: 99%